THE MACEDONIAN QUESTION: BETWEEN WESTERN AND EASTERN CULTURAL MEMORY OF ALEXANDER THE GREAT - Malešević, Matija (Serbian political thought, 2025)
This paper explores the “Macedonian Question” through the lens of the cultural memory of Alexander the Great. Rather than viewing it solely in political, legal, or geopolitical terms, the study examines the ideological and cultural constructions that shape contemporary understandings of the ancient legacy. Particular attention is given to the difference between Western and Eastern cultural memory: the Western tradition primarily presents Alexander as a conqueror and bearer of imperial order, while the Eastern tradition portrays him as a cultural mediator. The paper demonstrates that these divergent interpretations are not merely academic but carry strong political implications in the present regional and international context. Contemporary Macedonia emerges as a space where these narratives collide, most visibly in the dispute over its name and the Prespa Agreement, but also in broader processes of positioning the Balkans between West and East. Thus, the Macedonian Question today is not only a matter of national identity, but also a field in which global processes of cultural hegemony, ideological construction, and strategic competition are reflected.
Keywords: Macedonian Question; North Macedonia; Alexander the Great; Greece; Hellenism; Classicism; Cultural Memory; Prespa Agreement; Strategic Culture